2010
DOI: 10.1111/j.1365-2702.2010.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of risk of coronary heart disease among Jordanians

Abstract: Perception of risk of heart disease can greatly influence the decisions taken by adults in regard to their health care. Lack of accurate risk perception may prevent adults from considering the need for early preventive behaviours or seeking early life-saving interventions in the presence of coronary heart disease symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 22 publications
11
27
1
Order By: Relevance
“…Nearly twothirds of Jordanians aged 18 to 65 years are not vigorously active on a regular basis. 3,15,17,18,27,28 Our results are congruent with this statistic in that few participants reported that they engaged in vigorous activity (eg, running) or moderate activity (eg, fast walking and gardening). The low percentage of vigorous activity is not consistent with international physical activity recommendations.…”
Section: Discussionsupporting
confidence: 91%
“…Nearly twothirds of Jordanians aged 18 to 65 years are not vigorously active on a regular basis. 3,15,17,18,27,28 Our results are congruent with this statistic in that few participants reported that they engaged in vigorous activity (eg, running) or moderate activity (eg, fast walking and gardening). The low percentage of vigorous activity is not consistent with international physical activity recommendations.…”
Section: Discussionsupporting
confidence: 91%
“…25 This comparison suggests that the tool did have the ability to discriminate among samples with different levels of CV risk. It is possible that the perception of risk measured with the PRHDS instrument was an accurate reflection of their risk at baseline (mean score, 56), and thus, no change occurred.…”
Section: Discussionmentioning
confidence: 96%
“…A survey conducted by Ammouri et al [11] in four large cities in Jordan, for instance, assessed the awareness of adult Jordanians on the risk of coronary heart disease and its relationship to demographic variables and health behaviours. Significantly, almost half of the participants (n = 294) demonstrated a lack of knowledge regarding the risk of coronary heart disease, particularly women and young people.…”
Section: Discussionmentioning
confidence: 99%